THE EVOLUTION OF THE PUBLIC BANKING SECTOR OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. During the period of independence, several state-owned banks operated in Ukraine – from two in the 2000s to seven in 2013-2014 and 2024. Until 2008, the state’s share in the banking sector's assets was insignificant and amounted to approximately 6%. Since then, the share of state-owned banks has increased almost 10 times. Banks of the public sector are included in the list of critical infrastructure objects in the banking system and the list of authorized banks of Ukraine involved in work in the conditions of a special period.The purpose of the article is to determine the main trends in the development of the state banking sector in Ukraine during the period of independence.Methods. In the research process the following general scientific methods of knowledge were used, such as historical method (when studying the emergence and development of state banks in chronological order), generalization and comparison (when studying the essence of state banks, to compare the state banking sector of Ukraine and foreign countries), analysis (for assessment of the role of individual state-owned banks) and synthesis (for a generalized assessment of the share of the state-owned banking sector and the economic problems arising from it), a statistical method (in the study of quantitative indicators of the functioning of state-owned banks of Ukraine).The results. The main stages of the development of the state banking sector of Ukraine were studied: the reasons for the creation of state banks and the nationalization of private ones, the results of these decisions for the economy and the financial system, and the change state banking sector’s share in the banking system were analyzed. The place of individual state banks in the banking system by size and share of assets is highlighted.Conclusions. The main negative consequences of a high share of the state in the banking sector are summarized and the need to reform the state banking sector of Ukraine is formulated. The impracticality of privatizing the largest state-owned banks during the war has been substantiated.
Keywords: bank, state bank, bank with state share, state banking sector, nationalization, privatization, banking system, bank assets.